2012
DOI: 10.1158/1535-7163.mct-11-0873
|View full text |Cite
|
Sign up to set email alerts
|

Reexpression of Tumor Suppressor, sFRP1, Leads to Antitumor Synergy of Combined HDAC and Methyltransferase Inhibitors in Chemoresistant Cancers

Abstract: Metastatic solid tumors are aggressive and mostly drug resistant leading to few treatment options and poor prognosis as seen with clear cell renal cell carcinoma (ccRCC) and triple negative breast cancer (TNBC). Therefore the identification of new therapeutic regimes for the treatment of metastatic disease is desirable. ccRCC and TNBC cell lines were treated with the HDAC inhibitor romidepsin and the methyltransferase inhibitor decitabine, two epigenetic modifying drugs approved by the FDA for the treatment of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 46 publications
1
37
0
Order By: Relevance
“…Cell proliferation and anchorage independent growth can be inhibited if miR-27a is suppressed, which demonstrates that miR-27a exerts effects on cell proliferation [30]. The tumor suppressor gene SFRP1 functions as a negative regulator of Wnt signaling via its ability to form a heterodimer with Frizzled; this then prevents the formation of nonfunctional receptor complexes by Wnt proteins [31]. As Wnt antagonists, proteins in the SFRP family are endogenous modulators of Wnt signaling that compete with Wnt ligands for binding to the Frizzled receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Cell proliferation and anchorage independent growth can be inhibited if miR-27a is suppressed, which demonstrates that miR-27a exerts effects on cell proliferation [30]. The tumor suppressor gene SFRP1 functions as a negative regulator of Wnt signaling via its ability to form a heterodimer with Frizzled; this then prevents the formation of nonfunctional receptor complexes by Wnt proteins [31]. As Wnt antagonists, proteins in the SFRP family are endogenous modulators of Wnt signaling that compete with Wnt ligands for binding to the Frizzled receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic disorders, in contrast to genetic changes, are reversible and a role of the DNA demethylating agents such as 5-aza-2'-deoxycytidine has been established in the treatment of hematopoietic malignancies [3][4][5][6]. Cooper et al suggested that recombinant SFRP may be a novel therapeutic strategy for cancers with suppressed SFRP expression [25]. The DKK-1 gene, located on chromosome 11p15.1, is suppressed in a difference of human cancer cell lines and in numerous kinds of human cancers such as non-small cell lung carcinomas [26,27], human renal clear cell carcinoma [26], acute lymphoblastic leukemia [28] which also makes it a candidate tumor suppressor gene.…”
Section: Discussionmentioning
confidence: 99%
“…SFRP1 hypermethylation and downregulation are also associated with poor prognosis in several tumors (34,37,38). Moreover, SFRP1 is associated with tumor chemotherapy, and some antitumor drugs inhibit cell growth through the re-expression of SFRP1 (39)(40)(41). However, emerging evidence has indicated that SFRP1 may also be highly expressed in carcinomas and promote tumor proliferation or migration, such as in basal-like breast cancer (42), gastric cancer (43), and metastatic renal carcinoma (44).…”
Section: Discussionmentioning
confidence: 99%